The estimation methods of microfillers influence on cement stone properties/Mikroužpildų įtakos cementinio akmens savybėms analitinio įvertinimo principai - Deltuva, Juozas; Rudžionis, Žymantas (Journal of Civil Engineering and Management, 1997)
The concrete and cement microfillers are materials of different fineness, such as wastes of production or pulverized rocks. According to their influence on cement hardening process, they may be classified into inert microfillers or chemically active ones. The chemically active microfillers, such as silica fume, fly ashes and others, have more then 50% amorphous SiO2, that takes part in cement hardening process. Inert microfillers, such as granite, dolomite, sand dust and others, in most cases have no influence on the cement hydration. The usage of microfillers in concrete is common, but so far no clear dependence between the quantity of added microfillers and properties of concrete has been established. One of possible ways to estimate the microfillers influence on the products with cement binder is the structural element method. The structural element is the smallest cell, approximated to a spatial figure of regular form, that has all components with the same proportions, as in all the volume of heterogeneous material. The essence of this method is to divide the mix in to bigger particles, that are named “nuclei” of structural elements and take 50% of all mix volume, and smaller particles, that form cover layers of the nuclei and make up the rest of the volume of the mix. The dependence between the relative density of loose materials and relation (1) between the diameters of the bigger and smaller particles of the structural element has been estimated. This relation is changed when microfillers are added to the cement. There is a possibility to optimize relative density by (2), (3) and (4) relations, if the granulometric composition of the cement and microfillier is known. The experimental and calculated results of this optimization are shown in Table 1. The properties of pressed cement stone with inert microfillers admixture are presented in Table 2. Formulae for calculating the relative density (8) and compressive strength (11) of hardening cement have been estimated. The chemically active microfillers, such as silica fume, interact with Ca(OH)2 and form new CSH. The density and strength of cement stone increased after this interaction. The influence of chemically active microfillers on the relative density of the cement stone is given in (12). The density of cement stone increases to 4.5% and strength increases to 40.2%, if the quantity of inert microfillers in the cement paste reaches 10%. The density of cement stone increases to 7.4% and strength increases to 54.7%, if the quantity of chemically active microfillers in the cement paste reaches 10%. Article in Lithuanian. First Published Online: 26 Jul 2012